PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MURDER UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 1 KAMPAR TIMUR - Melta Fina; Betty Holiwarni; Rini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to determine Improved student achievement on thesubject of colloids with the implementation of cooperative learning model MURDERand the effect of the application of cooperative learning model MURDER to increasedstudent achievement on the subject of colloids in Class XI IPA SMAN 1 Kampar Timur.This research is a form of experimental research with the draft design randomizedcontrol group pretest-posttest. The study population was all students of class XI IPA atSMAN 1 Kampar Timur. The samples were students of class XI IPA 3 as experimentalclass and class XI IPA 4 as the control class. The experimental class was appliedcooperative learning model MURDER, while the control class using discussion method.Data were analyzed using t-test. Results from the study showed t count> t table (3.61>1.67) and the coefficient of influence by 17.33%, so it can be concluded theimplementation of cooperative learning model MURDER can improve the studentachievement on the subject of colloids in class XI IPA SMAN 1 Kampar Timur.Keywords: Cooperative Learning Model MURDER, Student Achievement, Colloid